Hidden ebook - Michaels, Fern (Lost and Found, 2021)
A page-turning new story from the bestselling author of No Way Out , perfect for fans of Nora Roberts and Danielle Steel ! Meet a brother and sister who are drawn into a treacherous mystery through an antique with a dark past, as they race against time to help a single mother and take down a ruthless couple bent on taking control of their family's legacy... At first glance, few would guess that Luna and Cullen Bodman are siblings. Cullen is efficient and serious while his younger sister Luna is a free spirit. When the two launch their furniture restoration shop/café—an offshoot of the family's longtime antique business—in an up-and-coming arts center, little do they know their unique talents may be their only defense against a dangerous betrayal. When Luna gets a strange sense about a piece Cullen just acquired, the two find themselves uniting to solve a mystery that has far-reaching consequences—never knowing there are some who'll stop at nothing to claim what they believe is theirs. No matter what, Luna and Cullen know they can rely on each other—and this time, their lives may depend on it...